1980
DOI: 10.2135/cropsci1980.0011183x002000020031x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Transformation of Soluble Carbohydrates during Germination Growth of Sorghum1

Abstract: Soluble components of sorghum (Sorghum bicolor (L.) Moench) seedlings growing in distilled water‐sand media were quantified with gas‐liquld‐chromatography. In light, peak levels of soluble component accumulation occurred in the roots in 4 days, in the endosperm in 8 days, and in the shoots in 10 days. Sucrose (2 µg/mg) was the predominant component in the dry seed. In 4‐day‐old seedlings, glucose and fructose levels were 15 and 20 µg/mg, respectively, in both shoots and roots. At l0 days, dhurrin levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The differences are probably due to the variations in maturity level of the sorghum caryopses (Newton et al . ). Springiness, hardness and grittiness showed significant differences in texture by the mouth.…”
Section: Resultsmentioning
confidence: 97%
“…The differences are probably due to the variations in maturity level of the sorghum caryopses (Newton et al . ). Springiness, hardness and grittiness showed significant differences in texture by the mouth.…”
Section: Resultsmentioning
confidence: 97%
“…During early seedling development in sorghum, the endosperm sugar content continuously depletes at the expense of increasing dhurrin content (Newton et al, 1980). Here, under full irrigation, dhurrin showed significant positive relationships to both monosaccharide sugars, glucose and fructose, and the disaccharide sugar sucrose at booting and postanthesis (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we report a reliable screening sand bioassay, using growth characteristics to screen 10-DAE (13-14 d old) seedlings of sorghum Table 3. Newton et al (1980) reported a reciprocal fluctuation between dhurrin and monosaccharide levels in the upper mesocotyl and coleoptile-shoot primordium regions of 4-d-old sorghum seedlings grown in small flats of sand and watered daily with distilled water in a growth chamber. In this study, seedling dhurrin contents showed an increasingly negative significant relationship to monosaccharide sugars under warm (experiment 3) and cold (experiment 4) temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of inorganic nutrients, early seedling growth is slowed (Newton et al, 1980). The availability of inorganic nutrients is crucial in sustaining growth and development very early on and throughout the plant life cycle.…”
Section: Seedling Growth Characteristicsmentioning
confidence: 99%